PHILOSOPHY OF MECHANISMS FOR STATE IMPACT IN MARKET ENVIRONMENT: EXPERIENCE OF UKRAINE - Korzhenko, Volodymyr; Kovalenko, Nataliia; Kozyrieva, Nataliia (Pressing Problems of Public Administration, 2020)
The problem of providing a proportional development of all the spheres of social being through public administration impact is growing in intensity in Ukraine, beginning from the mid-1990s i.e. in the period of the market environment emergence and inculcation, institutionalization of market relations and creation of market infrastructure. At that time, the idea of public administration mechanisms comes itno being and acquires the relevant content. Gradually comes the awareness of the fact that the state is able to affect in a variety of ways the socio-economic processes in a transformational society. The present research makes an attempt at summarizing some ideas that relate to application of mechanisms of state impact in a dynamically changing society. Essential differences between the mechanisms of public administration and state mechanisms of governance have been identified for further discussion by scientific community.